Redesign Interior Rumah Bahasa dan Tourist Information Center - Marietta Vincensia; Yusita Kusumarini; Anik Rakhmawati (Intra, 2018)
Rumah Bahasa and Tourist Information Center is a program of Surabaya city government. The government facilitates free education programs to prepare the ASEAN Free Trade Area (AFTA) and the ASEAN Economic Community (AEC). Rumah Bahasa and Tourist Information Center needs designed interior to maximalize space based on their activities and needs. The designer used stages of design thinking methods to simpifly analysis and design processes. Educative and communicative concept brings out the design theme, Jendela Dunia. This interior design serves fluent information and education activity by providing classroom, exhibition area, library and tourist information center. The design result creates linear space circulation with supportive atmosphere for information service and education activity.